The Impacts of Different Sorts of Art Education on Pupils’ Preference for 20th-Century Art Movements - Goran Kardum; Dubravka Kuščević; Marija Brajčić (Education Sciences, 2020)
The research presented here aims to determine how art education influences students’ preferences for the 20th-century art movements. An educational experiment that spanned through one school year was conducted on 200 primary school students. It included three types of intervention: observing works of art from the 20th century, introducing works of art using a puppet, and the students’ art activities/artwork based on the 20th-century art movements. The results show that the model of art education is an important factor in changing students’ preferences for the 20th century art movements. Students reacted positively to each kind of education, as evidenced in the wider acceptance of 20th-century art (abstract, fauvism, cubism, pop art, and surrealism). The type of education did not influence preferences (as much) when it came to classical art and visual works without artistic value. We concluded that puppets and independent creative work should be used more often in art education.